Increasing Market Transparency: The Role of the Internet and E-Commerce - Paula-Elena Diacon; Gabriel-Andrei Donici (CES Working Papers, 2013)
"Cyberspace" - a concept until recently considered somewhat obscure and fantasy, has become in the contemporary era common and one of the most exciting trends in business. The emergence and development of electronic commerce represented a huge step towards facilitating economic transactions and to the increase market transparency. The latter is one of the main pillars underlying the theoretical model of perfect competition, and thus of an efficient market. This article aims to investigate how electronic commerce has increased market efficiency by increasing transparency.
Keywords: L81; 330; electronic commerce; market transparency; Internet Romania